O jardim sensorial como espaço de aprendizagem para o ensino de Ciências Naturais e Biologia - Bettiol, Flavia Karolina Pereira Barreto (2020)
The main objective of this dissertation is to understand how the UFMT Sensory Garden can be used as a learning space for the teaching of Natural Sciences and Biology, which, like other areas, presents complex and often difficult content to be understood by everyone and, on the other hand, the teacher needs didactic-pedagogical resources that enable the best learning for his students. It is important that this teaching is accessible to all, in a way that guarantees inclusion. The UFMT Sensory Garden brings a proposal that enables inclusive education in this space, considering the adaptation of it to the different human senses, in the sense that the visitor can experience it in an educational and inclusive way. Through qualitative and participatory research, the space is being researched with the development of activities that can contribute to the production of a didactic sequence aimed at teaching in a sensory garden and that enables effective learning. In a field class held in 2019 at the Sensory Garden at UFMT, the research collaborators experienced the space presented. Thus, they participated in discussions about it, where four activities were developed: diagnosis prior to the visit, activity of perception of the sensory garden through the guided visit, application of the questionnaire to the participants and construction of mental maps. The activities made it possible for them to raise awareness about the proposal of the sensory garden, as well as to understand its pedagogical potential. The results obtained from the applied activities enabled the consolidation of the proposed educational product of the research - a didactic sequence for the sensory garden, developed so that this space has its educational purpose amplified.